The impact of value management on project success in felda projects - Othman, Nurul Izzaida (2015)
Implementation of value management practices can lead to improvement and innovation towards the initial target in term of cost, quality and performance of the project itself that actually set by the client and team of the project. The practices of value management also can help client understand the project’s objective, defining the needs and scope, improved team working together without any conflicts and the important things is to focus the main issues in order to ensure the quality of the project. Value management is defined as a brainstorming session that usually involved at the initial stages of a project to meet client’s needs and provide best value for money. The objective of this research is to identify the level of perception and practice of value management in the FELDA projects which can impact on project success. The person that involved in FELDA projects has been chosen as respondents. Quantitative method has been used in order to collect the data. The findings from this research can be a benchmark or systematic strategy to manage the project properly due to cost, time, specification and quality of the project